P53-independent induction of p21 fails to control regeneration and hepatocarcinogenesis in a murine liver injury model - Buitrago Molina, Laura Elisa; Marhenke, Silke; Becker, Diana; Geffers, Robert; Itzel, Timo; Teufel, Andreas; Jaeschke, Hartmut; Lechel, André; Unger, Kristian; Markovic, Jovana; Sharma, Amar Deep; Marquardt, Jens U.; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2021)
Background & Aims - A coordinated stress and regenerative response is important after hepatocyte damage. Here, we investigate the phenotypes that result from genetic abrogation of individual components of the checkpoint kinase 2/transformation-related protein 53 (p53)/cyclin-dependent kinase inhibitor 1A (p21) pathway in a murine model of metabolic liver injury. - Methods - Nitisinone was reduced or withdrawn in Fah-/- mice lacking Chk2, p53, or p21, and survival, tumor development, liver injury, and regeneration were analyzed. Partial hepatectomies were performed and mice were challenged with the Fas antibody Jo2. - Results - In a model of metabolic liver injury, loss of p53, but not Chk2, impairs the oxidative stress response and aggravates liver damage, indicative of a direct p53-dependent protective effect on hepatocytes. Cell-cycle control during chronic liver injury critically depends on the presence of both p53 and its downstream effector p21. In p53-deficient hepatocytes, unchecked proliferation occurs despite a strong induction of p21, showing a complex interdependency between p21 and p53. The increased regenerative potential in the absence of p53 cannot fully compensate the surplus injury and is not sufficient to promote survival. Despite the distinct phenotypes associated with the loss of individual components of the DNA damage response, gene expression patterns are dominated by the severity of liver injury, but reflect distinct effects of p53 on proliferation and the anti-oxidative stress response. - Conclusions - Characteristic phenotypes result from the genetic abrogation of individual components of the DNA damage-response cascade in a liver injury model. The extent to which loss of gene function can be compensated, or affects injury and proliferation, is related to the level at which the cascade is interrupted. Accession numbers of repository for expression microarray data: GSE156983, GSE156263, GSE156852, and GSE156252.